Languange Learning Adapatation Model In The Era of Society 5.0 - Firman Alamsyah Mansyur; Arsad Arsad; La Ode Achmad Suherman; Isti’anatul Himah; Istifatun Zaka; Zilani Zilani; Ilham Syarifuddin (Hasanuddin University, 2022)
This article aims to explain the adaptation model of language learning in the 5.0 society era. The method used is descriptive qualitative. The data used a library study on various studies of Language learning in the 5.0 era of society. The data were then identified and analyzed to build an understanding of the adaptation model of language learning in the 5.0 era as a form of response to future learning. The results of this study indicate that the adaptation model of Language learning to the era of society 5.0 is closely related to mastery of the field of Language which is integrated with mastery of the latest Information Technology, and mastery of 21st-century skills, namely creative thinking, critical thinking and problem solving, communication, and collaboration. However, the adaptation process and its results are largely determined by the ability of lecturers, students, and supporting facilities and infrastructure so that they can run well.